2018
DOI: 10.1111/bjh.15713
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine as part of conditioning of autologous stem cell transplantation in patients with aggressive lymphoma: a phase 2 study from the GELTAMO group

Abstract: Summary We conducted a phase 2 trial to evaluate the safety and efficacy of bendamustine instead of BCNU (carmustine) in the BEAM (BCNU, etoposide, cytarabine and melphalan) regimen (BendaEAM) as conditioning for autologous stem‐cell transplantation (ASCT) in patients with aggressive lymphomas. The primary endpoint was 3‐year progression‐free survival (PFS). Sixty patients (median age 55 [28–71] years) were included. All patients (except one who died early) engrafted after a median of 11 (9–72) and 14 (4–53) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…This result may be explained by the availability of several second-line therapies, such as ibrutinib, lenalidomide or bortezomib, which considerably improve the duration of survival in MCL patients. 24 Although the feasibility of BeEAM is clearly accepted, 16,17,25 its toxicity profile was not, as almost all conditioning regimens, prospectively compared to other conditioning regimen. We recently reported a large retrospective study on the toxicity of this regimen and we did not found an increased transplant related mortality which remained around 3%.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…This result may be explained by the availability of several second-line therapies, such as ibrutinib, lenalidomide or bortezomib, which considerably improve the duration of survival in MCL patients. 24 Although the feasibility of BeEAM is clearly accepted, 16,17,25 its toxicity profile was not, as almost all conditioning regimens, prospectively compared to other conditioning regimen. We recently reported a large retrospective study on the toxicity of this regimen and we did not found an increased transplant related mortality which remained around 3%.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…In T-cell lymphomas, ASCT in first remission is the preferred consolidation option to improve outcomes, with one study reporting 5-y PFS of up to 49% in AITL [2]. One option as a conditioning regimen before ASCT for these entities is the BeEAM regimen (bendamustine, etoposide, cytarabine, and melphalan) as it offers comparable efficacy to the BEAM (BCNU, etoposide, cytarabine, and melphalan) regimen, avoids BCNU-related pulmonary toxicities, and its commercial availability is decisively more reliable [3][4][5][6][7][8]. However, various other drug combinations have been or are being evaluated [9,10].…”
Section: Cd30+ Lymphomas Comprise Hodgkin Lymphomas (Hl) But Also a V...mentioning
confidence: 99%
“…The BeEAM regimen, through its global safety profile and the reduced recruitment rate consecutive to iDSMB recommendation, led to prematurely stop the trial. The only prospective trial evaluating this conditioning regimen in aggressive lymphoma 5 reported a high toxicity rate with 39 SAEs in 60 (65%) patients including two toxicity‐related mortalities. Infectious SAEs were observed in 18 (30%) patients.…”
Section: Figurementioning
confidence: 99%